Effect of Seasons on Grain Infestation and Biochemical Stored Wheat in’ Western Rajasthan Composl’tI’OnI 0f - Nahla, M K; Ameta, O P; Joshi, A; Dadeech, L N (Annals of Arid Zone, 2016)
Studies conducted during 1997-99 on the seasonal effect on grain infestation and biochemical composition of grains revealed that the total infestation of grains due to Rhizoperlha dOlllinica (Fab.), Trogoderllla granarilllll Everts, Silo/roga cerealella (Oliver), Tribolilllll caslanelllll (Herbst) and SilOphillls oryzae Linn. was lowest (6.36%) during June-July with a mean protein and alcoholic acidity of 11.72 and 0.083%, respectively. The grain infestation increased to 21.17% during September-October and reduced protein content of the grain to 8.23% and increased the alcoholic acidity to 0.097%. The infestation declined to 12.61% in January-February and caused slight increase in the protein (9.00%), but did not influence alcoholic acidity of tlie grains.